Identifying opportunities for sustainable intensification of mixed farming systems in the Mid-Hills of Nepal by optimal use of water in agriculture - Veenings, Lois; Cossu, Alessandra; Shrestha, Nirman; Adhikari, Tikaram; López Ridaura, Santiago; Groot, Jeroen C.J. (International Maize and Wheat Improvement Center, 2023)
Food production and rural livelihoods' food security in Nepal face numerous threats for various reasons. Similar to global trends, the country contends with unpredictable weather patterns, including heat and drought stress on plants, as well as heavy precipitation. Around 80% of Nepal’s population is dependent on subsistence farming for their livelihood, while only 24% of all arable land is irrigated (Suhardiman et al., 2015).